A STUDY OF THE SPEED OF MOVEMENT OF VEHICLES ON HIGHWAYS - Eshquvvatov Ulug‘bek Abdulla o‘g‘li (Web of Journals Publishing, 2025)
The master road serves as a basis for indicating the most important operational indicators of the transport process on roads, as well as technical service parameters. The design is based on the category of roads, traffic conditions, and terrain. At the same time, it characterizes the maximum permissible speed of movement of one vehicle on the road with normal contact of the wheel with the road, while maintaining the vehicle.
Keywords: Highways, vehicles, traffic speed, frequency, curvature, distance, categorization, speed.